Evaluation of the dehydrating properties of some sililating agents in the synthesis of imidazole-5-one - Hovhannisyan, A. A.; V. O. Topuzyan; V. M. Ghazoyan; G. Sh. Hovhannisyan (ՀՀ ԳԱԱ հրատ.)
The effect of solvent, some additives and temperature on the dehydrating properties of dimethyldichlorosilane (DMDCS), trimethylchlorosilane (TMCS) and 1,1,1,3,3-hexamethyldi- silazane (HMDS) in the synthesis of 1-benzyl-2-phenyl-4-benzylidene-5-imidazolone from benzylamide N-benzoyl-α,β-dehydrophenylalanine was investigated. It was found that in the case of using DMDCS or TMHS as a reagent, the formation of a by-product - 2-phenyl-4-benzylidene-5-oxazolone was observed.Ուսումնասիրված է լուծիչի, ջերմաստիճանի և մի քանի հավելանյութերի ազդեցությունը դիմեթիլդիքլորսիլանի (ԴՄԴՔՍ), տրիմեթիլքլորսիլանի (ՏՄՔՍ) և 1,1,1,3,3,3-հեքսամեթիլդիսիլազանի դեհիդրատացնող հատկությունների վրա N-բենզոիլ-α,β-դեհիդրոֆենիլալանինից 1-բենզիլ-2-ֆենիլ-4-բենզիլիդեն-5-իմիդազոլոնի ստացման ռեակցիայում: Պարզված է, որ ԴՄԴՔՍ և ՏՄՔՍ օգտագործման դեպքում, բացի նպատակային իմիդազոլոնից, գոյանում է նաև կողմնակի արգասիք՝ 2-ֆենիլ-4-բենզիլիդեն-5-օքսազոլոն: Исследовано влияние растворителя, некоторых добавок и температуры на дегидратирующие свойства диметилдихлорсилана (ДМДХС), триметилхлорсилана (ТМХС) и 1,1,1,3,3,3-гекса-метилдисилазана (ГМДС) при синтезе 1-бензил-2-фе-нил-4-бензилиден-5-имидазолона из бензиламида N-бензоил-α,β-дегидрофенил-аланина. Установлено, что в случае применения в качестве реагента ДМДХС или ТМХС наблюдается образование побочного продукта – 2-фенил-4-бензилиден-5-оксазолона.
Keywords: Organic Chemistry